Flight Capacity of Bactrocera dorsalis (Diptera: Tephritidae) Adult Females Based on Flight Mill Studies and Flight Muscle Ultrastructure. Issue 1 (8th October 2015) - Chen, Min; Chen, Peng; Ye, Hui; Yuan, Ruiling; Wang, Xiaowei; Xu, Jin
Abstract : The oriental fruit fly, Bactrocera dorsalis (Hendel) (Diptera: Tephritidae), is considered a major economic threat in many regions worldwide. To better comprehend flight capacity of B. dorsalis and its physiological basis, a computer-monitored flight mill was used to study flight capacity of B. dorsalis adult females of various ages, and the changes of its flight muscle ultrastructures were studied by transmission electron microscopy. The flight capacity (both speed and distance) changed significantly with age of B. dorsalis female adults, peaking at about 15 d; the myofibril diameter of the flight muscle of test insects at 15-d old was the longest, up to 1.56 µm, the sarcomere length at 15-d old was the shortest, averaging at 1.37 µm, volume content of mitochondria of flight muscle at 15-d old reached the peak, it was 32.64%. This study provides the important scientific data for better revealing long-distance movement mechanism of B. dorsalis.